Rara and Her Bedtime Story Journey - Rudi Suherman (Universitas Cokroaminoto Palopo, 2020)
This study reported four–week English bedtime story of Rara, a young English language learner from Indonesia. A case study approach was employed in this study. Fitri, Rara’s mother, was asked to read five different English stories to her on the basis of the period of four weeks regularly. These stories were given as media for children to have comprehensible input. The data were taken from daily journal written by the mother and a semi-structure interview in which was then analyzed and interpreted. The result showed that the child was able to follow the storylines and was able to comprehend them. The story also helped the child acquiring some English vocabularies and fixed utterances naturally. Hence, English bedtime story program can be considered as an alternative way in introducing English to EFL young learners.